2011
DOI: 10.1007/s00134-011-2207-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of different continuous positive airway pressure helmets equipped with safety valves during failure of fresh gas supply

Abstract: To minimize CO(2) rebreathing during disconnection of the fresh gas supply while performing helmet CPAP, it is desirable to utilize large helmets with a large anti-suffocation valve. Monitoring and alarm systems should be employed for safe application of helmet CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The presence of an antisuffocation valve ( Figure S1) limits the CO 2 rebreathing, but cannot prevent the loss of PEEP in case of gas flow interruption [22]. In this case, the adoption of larger valves allows for a lower CO 2 rebreathing, but also a higher reduction in FiO 2 [25]. When CPAP is administered by means of mechanical ventilators, it is generally not advisable to use the helmet [8,22] because the higher compliance of the helmet may cause a delay between the delivered inspiratory flow and patients' inspiratory effort, which can cause patient-ventilatory asynchrony.…”
Section: Cpap Side Effects and Helmet Pitfallsmentioning
confidence: 99%
“…The presence of an antisuffocation valve ( Figure S1) limits the CO 2 rebreathing, but cannot prevent the loss of PEEP in case of gas flow interruption [22]. In this case, the adoption of larger valves allows for a lower CO 2 rebreathing, but also a higher reduction in FiO 2 [25]. When CPAP is administered by means of mechanical ventilators, it is generally not advisable to use the helmet [8,22] because the higher compliance of the helmet may cause a delay between the delivered inspiratory flow and patients' inspiratory effort, which can cause patient-ventilatory asynchrony.…”
Section: Cpap Side Effects and Helmet Pitfallsmentioning
confidence: 99%
“…An antisuffocation valve, which allows room air to enter the helmet during any interruption of gas flow, limited the CO 2 rebreathing but not the loss of external PEEP [9]. In a subsequent study, Milan and colleagues [10], testing three commercially available helmets supplied with antisuffocation valves, found that the helmet with the largest valve had lower CO 2 rebreathing but a greater reduction in oxygenation in case of interruption of the gas flow.…”
Section: Resultsmentioning
confidence: 99%
“…Anything that increases helmet ventilation (i.e., air leak and delivery of fresh gas) may decrease the inspired partial pressure of CO 2 . An anti-suffocation valve, a safety valve that allows air to enter into the helmet during any interruption of gas flow, may limit CO 2 rebreathing [144-146].…”
Section: Dead Space Interface Volume and “Vented And Non-vented Mask”mentioning
confidence: 99%